Ultradian rhythms of CRH PVN neuron activity, behavior, and stress hormone secretion - Shaojie Zheng; Caroline M. B. Focke; Calvin K. Young; Isaac Tripp; Dharshini Ganeshan; Emmet M. Power; Daryl O. Schwenke; Allan E. Herbison; Joon S. Kim; Karl J. Iremonger (Proceedings of the National Academy of Sciences, 2025)
The stress axis is always active, even in the absence of any threat. This manifests as hourly pulses of corticosteroid stress hormone secretion over the day. Corticotropin-releasing hormone (CRH) neurons in the paraventricular nucleus of the hypothalamus (CRH PVN ) control both the neuroendocrine stress axis as well as stress-associated behaviors. However, it is currently unclear how the resting activity of these neurons is coordinated with both spontaneous behavior and ultradian pulses of corticosteroid secretion. To investigate this, we performed fiber photometry recordings of CRH PVN neuron activity in Crh-Ires-Cre mice and a newly generated line of Crh-Ires-Cre rats. In both mice and rats, CRH PVN neurons displayed an ultradian rhythm of activity with reoccurring upstates of activity approximately once per hour over the 24-h day. Upstates in activity were coordinated with increases in animal activity/arousal. Chemogenetic activation of CRH PVN neurons was also sufficient to induce behavioral arousal. In rats, increases in CRH neural activity preceded some pulses of corticosteroid secretion but not others. Thus, while CRH PVN neurons display an ultradian rhythm of activity over the 24-h day that is coordinated with behavioral arousal, the relationship between CRH PVN activity and pulses of corticosteroid secretion is not one-to-one.